Pluralistic Ethics and Fiqh of Nationality: Lirboyo Islamic Boarding School's Efforts to Build a National Episteme Based on Jurisprudence - Yaqin, Haqqul; Ja'far, Suhermanto (AL-TAHRIR, 2024)
The implementation of Islamic law through the establishment of the Unitary State of the Republic of Indonesia is a long-standing historical phenomenon. This process has led to social fragmentation, resulting in the disintegration of the Indonesian people both within the nation and state. This article examines the progressive response of the Lirboyo Islamic Boarding School alumni and student communities to the democratic process by introducing the fiqh of nationality, particularly in light of the rise of salafism ideology. Specifically, this article focuses on the use of the fiqh of nationality as a logical counter to the puritanism paradigm, which views human subjectivity as limited to carrying out God's commands. The aim is to identify patterns in the exploration of the meaning of normative texts that promote social and humanist goals and religious values. Additionally, this article reveals social strategies employed in representing the fiqh of nationality in the public sphere. A qualitative approach was employed as a method to discover important aspects of text exploration strategies and patterns. To provide more detailed text patterns and exploration, interviews were conducted with several senior students who initiated the discourse on the fiqh of nationality, as well as with several caregivers. The research findings indicate that the fiqh of nationality emerged as a result of a dynamic dialectic with citizenship phenomena at the local and global levels, which seeks to counter the tendencies of certain groups to generate monolithic religious propositions and understandings.